Study Cekaman Salinitas Terhadap Mutan Padi Pada Kondisi In Vitro - Yunita, Rossa; Khumaida, Nurul; Sopandie, Didy; Mariska, Ika (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
In vitro selection using of salt (NaCl) has been used to select plants that tolerate salinity, so that effective selection process. The purpose of this study was to obtain information about the mechanism of salinity tolerance in rice in vitro conditions. This study consisted of two experiments, they are the selection of salinity tolerance somaclone putative mutants in vitro and study of salinity tolerance mechanism results in in vitro selection. The tolerant plants after being treated NaCl show response to the accumulation of proline is more, the content of K, Mg and Ca which tends to remain and Na content is lower, stomata density is fewer and the length and width ratio stomata is greater.